PENGARUH HALAL SUPPLY CHAIN TERHADAP PERILAKU KONSUMEN MUSLIM DALAM MENGONSUMSI PRODUK MAKANAN HALAL DI JABODETABEK - Radella Kus Damalis Abdullah (2023)
Muslim consumers in consuming food products tend to choose foods that are clearly halal, but not all Muslim consumers know the process of making these food products until they are in the hands of consumer. The purpose of this study is to examine the effect of the Raw Material Selection Process, Production Process, Packaging Process, Halal Labeling Process, and Distribution Process on the behavior of Muslim consumers in consuming food products in Jabodetabek. This study uses a Muslim population who is also a Muslim consumer in Jabodetabek who consumes food products. The data that researcher used in this study is primary data with a total of 164 respondents with a quantitative approach. Technique of the data collection will be using questionnaire with likert scale. The data analysis technique uses PLS technique. The result of the hypothesis tests are the Raw Material Selection Process is significant, Production Process is not significant, Packaging Process is not significant, Halal Labeling Process is significant, and Distribution Process have a significant effect on Muslim Consumer Behavior in Consumption.